Probiotics Support Resilience of the Oral Microbiota during Resolution after Experimental Gingivitis - A Randomized, Double-Blinded, Placebo-Controlled Trial - Lundtorp Olsen C; Massarenti L; Vendius VFD; Gürsoy UK; Van Splunter A; Bikker FJ; Gürsoy M; Damgaard C; Markvart M; Belstrøm D (Switzerland, 2025)
The present study aims to test whether probiotics protect against experimental gingivitis incited by 14 days of oral hygiene neglect and/or subsequently support the restoration of oral homeostasis. Eighty systemically and orally healthy participants refrained from oral hygiene procedures for 14 days, followed by 14 days with regular oral hygiene procedures. Additionally, participants consumed either probiotics (n = 40) or placebo (n = 40) throughout the trial. At baseline, day 14, and day 28, supragingival plaque score and bleeding-on-probing percentage (BOP %) were registered, and supragingival plaque and saliva samples were collected. The supragingival microbiota was characterized using 16S sequencing, and saliva samples were analyzed for levels of pro-inflammatory cytokines and proteases. At day 28, the relative abundance of Lautropia (p = 0.014), Prevotella (p = 0.046), Fusobacterium (p = 0.033), and Selenomonas (p = 0.0078) genera were significantly higher in the placebo group compared to the probiotics group, while the relative abundance of Rothia (p = 0.047) species was associated with the probiotics group. Streptococcus sanguinis was associated with the probiotics group, while Campylobacter gracilis was associated with the placebo group. No difference was observed in salivary cytokines, albumin, or any enzyme activity. The present study suggests that probiotics support the resilience of the oral microbiota in the resolution period after gingivitis.